2018
DOI: 10.1093/sleep/zsy009
|View full text |Cite
|
Sign up to set email alerts
|

Sleep findings in Brazilian children with congenital Zika syndrome

Abstract: Considering the well-known consequences of poor sleep quality on health in several populations, the presence of sleep disorders should be considered in CZS using multidisciplinary treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…The percentage of infants in our sample who had difficulty with sleep, the reported number of hours the infants slept at night and during the day, and the amount of time it took for them to fall asleep all resembled a larger sample of typically developing infants in Brazil [ 11 ]. However, these findings contrast with reports of sleep issues in a larger sample of children with CZS reported by Pinato and colleagues [ 12 ], who found that the children with CZS were significantly more likely to be reported as having sleep problems and having shorter total sleep time and shorter nocturnal sleep duration that a typically developing control group. These differences in findings may be due to differences in sample size between the two studies.…”
Section: Resultscontrasting
confidence: 99%
“…The percentage of infants in our sample who had difficulty with sleep, the reported number of hours the infants slept at night and during the day, and the amount of time it took for them to fall asleep all resembled a larger sample of typically developing infants in Brazil [ 11 ]. However, these findings contrast with reports of sleep issues in a larger sample of children with CZS reported by Pinato and colleagues [ 12 ], who found that the children with CZS were significantly more likely to be reported as having sleep problems and having shorter total sleep time and shorter nocturnal sleep duration that a typically developing control group. These differences in findings may be due to differences in sample size between the two studies.…”
Section: Resultscontrasting
confidence: 99%
“…The primary studies grouped in this review showed evidence of exposure to ZIKV in the fetal period and the post exposure effects in newborns (NBs) and breastfeeding children. Neurological abnormalities and/or congenital malformations were present in all studies (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . Microcephaly (62.8%) (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was predominant, however other studies have reported the occurrence of alterations in the central nervous system and multiple malformations (12,(21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in ten studies (62.5%) was observed the presence of microcephaly; in seven (43.7%), ocular alterations such as nystagmus or visual impairment; in four (25%), ventriculomegaly; in three (18.7%), subcortical calcifications, alterations in fine motor development, arthrogryposis; in two (12.5%), cortical development malformation, cerebral atrophy, cerebral palsy with microcephaly, changes in motor and cognitive development and hearing loss; and in one (6.25%), convulsions, restless movements at 12 months without microcephaly, changes in sleep pattern, severe hypertonia and heart malformation (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations